Accuracy of Hepatic Angiogram During Trans-Arterial Chemoembolization (TACE) With Triphasic CT Scan in Detecting Tumor Size and Number of Lesions in Diagnosed Hepatocellular Carcinoma Patients - Irshad, Rashida; Azmat, Uzma; Rakhshani, Abdul Qayoom; Raza, Muhammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the accuracy of the hepatic angiogram during trans-arterial chemoembolization (TACE) with triphasic computed tomography (CT) scan in detecting tumor size and number of lesions in diagnosed hepatocellular carcinoma (HCC) patients.Study Design: Cross-sectional study.Place and Duration of Study: Department of Radiology, Memon Medical Institute Hospital, Karachi, Pakistan, from Feb to July 2024.Methodology: Both male and female patients aged 40 to 80 years with HCC were assessed based on serum Alpha-Fetoprotein (AFP) levels> 200 ng/ml with a duration of at least three months. All patients were referred for TACE and underwent pre-procedural imaging with triphasic CT to detect the tumor size and number of lesions. Results of the diagnosis were recorded in a predesigned proforma. Results: A total of 133 patients were included, aged 59.09±10.36 years, with a mean HCC duration of 4.45±1.22 months, and an average lesion size of 5.53±0.846 cm. The overall accuracy of hepatic angiograms during TACE with triphasic CT scans in detecting tumor size and the number of lesions among diagnosed HCC was 74% (n=98). Accuracy was significantly high in those cases whose duration of HCC was above 5 months (p-value=0.015).Conclusion: The study demonstrated that hepatic angiography during TACE provides a reasonable accuracy rate of 74% in detecting tumor size and the number of lesions in HCC patients, with particularly high accuracy in patients with prolonged disease duration.